A systematic review of telehealth applications in hospital medicine. Issue 4 (6th March 2022) - Gutierrez, Jeydith; Rewerts, Kelby; CarlLee, Sheena; Kuperman, Ethan; Anderson, Melver L.; Kaboli, Peter J.
Abstract: Background: Despite the proliferation of telehealth, uptake for acute inpatient services has been slower. Hospitalist shortages in rural and critical access hospitals as well as the COVID‐19 pandemic have led to a renewed interest in telehealth to deliver acute inpatient services. Understanding current evidence is crucial for promoting uptake and developing evidence‐based practices. Objective: To conduct a systematic review of telehealth applications in acute inpatient general medicine and pediatric hospital wards and synthesize available evidence. Data Sources: A search of five databases (PubMed, CINAHL, Embase, Scopus, and ProQuest Theses, and Dissertations) using a combination of search terms including telemedicine and hospital medicine/inpatient care keywords yielded 17, 015 citations. Study Selection and Data Extraction: Two independent coders determined eligibility based on inclusion and exclusion criteria. Data were extracted and organized into main categories based on findings: (1) feasibility and planning, (2) implementation and technology, and (3) telehealth application process and outcome measures. Results: Of the 20 publications included, three were feasibility and planning studies describing the creation of the program, services provided, and potential cost implications. Five studies described implementation and technology used, including training, education, and evaluation methods. Finally, twelve discussed process and outcome measures, including patient and provider satisfaction and costs. Conclusion: Telehealth services for hospital medicine were found to be effective, well received, and initial cost estimates appear favorable. A variety of services were described across programs with considerable benefit appreciated by rural and smaller hospitals. Additional work is needed to evaluate clinical outcomes and overall program costs.